Authoritarian capitalism : sovereign wealth funds and state-owned enterprises in east asia and beyond - Carney, Richard D. (2018)
"Since 1945, the liberal-democratic model of capitalism spread across the globe, ultimately prevailing over communism. Over the past two decades, a new statist-authoritarian model has begun diffusing across East Asia. Rather than rejecting capitalism, authoritarian leaders harness it to uphold their rule. Based on extensive research of East Asia's largest corporations and sovereign wealth funds, this book argues that the most aggressive version of this model does not belong to China. Rather, it can be found in Malaysia and Singapore. Although these countries are small, the implications are profound because one-third of all countries in the world possess the same type of regime. With an increasing number of these authoritarian regimes establishing sovereign wealth funds, their ability to intervene in the corporate sectors of other countries is rapidly expanding"--
"Authoritarian Capitalism Sovereign Wealth Funds and Corporate Intervention in East Asia and Beyond Since 1945, the liberal-democratic model of capitalism spread across the globe, ultimately prevailing over communism. Over the past two decades, a new statist- authoritarian model has begun diffusing across East Asia. Rather than rejecting capitalism, authoritarian leaders harness it to uphold their rule. Based on extensive research of East Asia's largest corporations and sovereign wealth funds, this book argues that the most aggressive version of this model does not belong to China. Rather, it can be found in Malaysia and Singapore. Although these countries are small, the implications are profound because one-third of all countries in the world possess the same type of regime. With an increasing number of these authoritarian regimes establishing sovereign wealth funds, their ability to intervene in the corporate sectors of other countries is rapidly expanding"--
Includes bibliographical references (pages 278-311) and index.
Keywords: Capitalism -- Political aspects -- East Asia; Authoritarianism -- East Asia; Globalization -- East Asia